2017
DOI: 10.1093/femspd/ftx111
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis plasmid-encoded protein pORF5 protects mitochondrial function by inducing mitophagy and increasing HMGB1 expression

Abstract: Chlamydia trachomatis, an obligate intracellular pathogen, has various effective strategies to regulate host cell death signalling pathways that ensure completion of their growth cycle. Mitochondrial autophagy (mitophagy) is responsible for elimination of dysfunctional and impaired mitochondria, and this process plays a critical role in cell survival via restriction of the mitochondrial apoptotic pathway. However, the specific molecular mechanisms are not entirely understood. In the present study, we observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Examples include activating transcription factor 1, 2, and 6 (ATF-1/2/6), p53, MITF1, DDIT3, ELK1, and high mobility group-box protein 1 (HMGB1) and so on (Zarubin and Han, 2005). Consistent with the changes of these transcription factors, pORF5 protein was proved to be able to up-regulate DDIT3, activate the expression of unfolded protein and its downstream molecules ATF4, ATF6, and CHOP, thereby promoting cell autophagy (Wen et al, 2020), and also up-regulate the expression of HMGB1 and induce mitochondrial autophagy to resist apoptosis (Lei et al, 2017). MAPK pathway deeply influences the cellular physiological processes, and can active by pORF5 secreted by C. trachomatis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Examples include activating transcription factor 1, 2, and 6 (ATF-1/2/6), p53, MITF1, DDIT3, ELK1, and high mobility group-box protein 1 (HMGB1) and so on (Zarubin and Han, 2005). Consistent with the changes of these transcription factors, pORF5 protein was proved to be able to up-regulate DDIT3, activate the expression of unfolded protein and its downstream molecules ATF4, ATF6, and CHOP, thereby promoting cell autophagy (Wen et al, 2020), and also up-regulate the expression of HMGB1 and induce mitochondrial autophagy to resist apoptosis (Lei et al, 2017). MAPK pathway deeply influences the cellular physiological processes, and can active by pORF5 secreted by C. trachomatis.…”
Section: Discussionmentioning
confidence: 89%
“…Our previous studies also verified that pORF5 influenced the expression of host proteins (Zou et al, 2018). These alternated proteins take part in cellular processes including apoptosis and autophagy (Lei et al, 2017), indicating that pORF5 plays a key role in the pathogenesis of C. trachomatis.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Currently, it is believed that C. trachomatis can proliferate itself by resisting host cell apoptosis, and some studies have also shown that the enlargement of Chlamydia inclusions would promote cell apoptosis. 50 In this study, we combined our previous work 51,52 to propose the scientific hypothesis that persistent C. trachomatis infection-related differential lncRNAs might be involved in host cell antiapoptotic activity. Subsequently, we used a microarray platform to perform transcriptome analysis of lncRNAs and protein-coding genes in an in-vitro cell model of persistent C. trachomatis infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we combined our previous work 51 , 52 to propose the scientific hypothesis that persistent C . trachomatis infection‐related differential lncRNAs might be involved in host cell antiapoptotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lei et al demonstrated that C. trachnomatis plasmid-encoded protein pORF5 up-regulated the expression of high mobility group box 1 (HMGB1) which induces mitophagy and inhibits apoptosis of host cells (Table 1, Figure 1). 47 These findings suggest that C. trachnomatis could manipulate host cell death to usurp enough nutrients generated via autophagy for their survival and replication.…”
Section: Introductionmentioning
confidence: 98%